KORELASI TEMPERAMEN BAYI DENGAN MATERNAL SELF EFFICACY PADA IBU REMAJA DI BANGKA SELATAN - Puspasari, Jehan (Jurnal Kesehatan Holistic, 2017)
The purpose of this study was to identify the relationship between infant temperamment with maternal self efficacy in adolescent mothers. This cross-sectional study used consecutive sampling technique with 100 primipara teenage mother. The measurement tools used were structured questionnaires, demographic questionnaires, Maternal Efficacy Questionnaire (MEQ), Edinburgh Postnatal Depression Scale (EPDS) and Infant Characteristic Questionnaire (ICQ). The baby's temperament variable and mother's self-confidence were analyzed using chi-square and logistic regression. The results showed that there was a significant relationship between infant temperamment with maternal self efficacy in adolescent mother with p value 0,001. Infant temperament greatly affects teen mom's confidence. Easy infant temperament has an effect on improving maternal self efficacy compared to difficult baby temperaments.